Role of Leadership Style in Employee Retention in Senegal - Manga, Ismaïla (European Journal of Human Resource, 2024)
Purpose: The aim of the study was to assess the role of leadership style in employee retention in Senegal. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that leadership style plays a crucial role in employee retention. Effective leadership fosters a positive work environment, which significantly influences employees' decisions to stay with an organization. Transformational leadership, characterized by inspiring and motivating employees, tends to enhance job satisfaction and commitment, thereby reducing turnover rates. Leaders who prioritize open communication, provide constructive feedback, and recognize employees' contributions create a supportive atmosphere that encourages loyalty. Conversely, authoritarian leadership styles, which rely on strict control and limited employee autonomy, often result in higher stress levels and job dissatisfaction, leading to increased turnover. Additionally, leaders who invest in employees' professional development and show genuine concern for their well-being contribute to a sense of belonging and long-term commitment. Therefore, cultivating a leadership style that emphasizes empathy, empowerment, and employee engagement is essential for retaining a talented and motivated workforce. Implications to Theory, Practice and Policy: Social exchange theory, self-determination theory and path-goal theory may be used to anchor future studies on assessing the role of leadership style in employee retention in Senegal. Organizations should prioritize leadership development programs that cultivate transformational and authentic leadership qualities among managers and supervisors. Policymakers and HR practitioners can play a crucial role in shaping organizational policies and practices that support employee retention.